KONDISI OPTIMUM ADSORPSI-FLUIDISASI ZAT WARNA LIMBAH TEKSTIL MENGGUNAKAN ADSORBEN JANTUNG PISANG - Dheasy Herawati; Setyo Dwi Santoso; Ilma Amalina (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2018)
To show that banana inflorescence has effective adsorbent for the adsorption of dyes (congo red, remazol yellow, remazol black and methylene blue) from textile dyes waste and also to detrmine the optimum conditions of variety of pH (4-10), temperature (30°C-90°C), and contact time (15-105 minute) on the percentage adsorption capacity of banana inflorescence. Textile dyes waste and their degradation products such as aromatic amines are highhly carcinogenic. Adsorption-fluidization is a new technology for treatment of waste water containing different types of dyes. Adsorption-fluidization process is adopted for adsorption of dyes from the textile dyes waste using banana inflorescence in treated form and were analysed by Utraviolet-Visible Spectroscopy. The results showed that the optimum condition from adsorption process of Congo Red dye by banana inflorescence was reached at pH 5 (1.78%), temperature 60°C (1.51%) and 45 minute contact time (1.63%). While Remazol Yellow dye optimum at pH 9 (4.29%), temperature 50°C (4.65%) and 75 min (1.83%). Another dye, Methylene Blue showed the optimum condition at pH 9 (0.36%), temperature 40°C (0.22%) and 45 min contact time of adsorption (0.43%). The last, Remazol Black dye was reached at pH 5 (0.56%), temperature 40°C (0.56%) and 75 min contact time (0.56%).